"A Joyous Star-Spangled-Bannerism": Emma Juch, Opera in English Translation, and the American Cultural Landscape in the Gilded Age. Issue 2 (4th June 2014) - TURNER, KRISTEN M.; Preston, Katherine K.; Katz, Mark
Abstract Soprano Emma Juch (1860–1939), famous in the 1880s and 1890s, combined singing in concerts and festivals with a short English-language operatic career. Because Juch exemplifies a typical prima donna of the late nineteenth century, her life provides a perspective on the American cultural landscape that a focus on star performers cannot capture. Like all female singers, she had to negotiate between competing stereotypes about divas and the nineteenth-century distrust of women who led public lives. In response to these pressures, she constructed an image of a vigorous American singer who nevertheless understood her expected role in society. During the Gilded Age, opera's place in American culture was changing. Foreign-language opera became increasingly associated with wealth, the highest performance quality, and sometimes even cultural and moral uplift, whereas English-language opera suggested popular entertainment for the middle class and mediocre performance standards. The American Opera Company and Juch's own Emma Juch English Grand Opera Company attempted to fight against these assumptions and center opera in English performed by native singers as an important component of a distinctly American musical tradition. She was unsuccessful, however, and Juch's career, which began with great promise, lost momentum after her opera troupe folded and she slid into obscurity.